Programming 32-bit microcontrollers in C : - Di Jasio, Lucio (Elsevier, 2008)
The new 32-bit microcontrollers bring the promise of more speed and more performance while offering an unprecedented level of compatibility with existing 8 and 16-bit PIC microcontrollers. In sixteen engaging chapters, using a parallel track to his previous title dedicated to 16-bit programming, the author puts all these claims to test while offering a gradual introduction to the development and debugging of embedded control applications in C.